First experiences with a new adjustable length titanium ossicular prosthesis (ALTO) - Praetorius, Mark; Kirchenbauer, Sabrina S.; Buß, Stefanie; Klingmann, Christoph; Plinkert, Peter K.; Baumann, Ingo (Acta oto-laryngologica, 2010)
Conclusions: The new length-adjustable titanium prosthesis can give good results in terms of hearing results in ossiculoplasty. The possibility to readjust the length intraoperatively was seen as a good feature. Objective: Hearing results of ossiculoplasty with a newly designed prosthesis in 14 patients were evaluated. The prosthesis is designed to allow adjustment of length in situ. Methods: A retrospective pilot study was carried out, comparing the preoperative and postoperative audiological and clinical results with an age- and pathology-matched group. The setting was the Department of Otolaryngology at the University of Heidelberg Medical Center, a tertiary referral center. In all, 14 patients underwent tympano-ossiculoplasty in which autologous reconstruction was not an option. The ossiculoplasty was performed as a therapeutic measure with the new titanium prosthesis. We evaluated the air-bone gap closure as established from preoperative and postoperative audiograms. We also looked at the clinical aspect of the tympanic membrane. Results: The average air-bone gap came to a closure within 15 dB in 43% of the cases (6 of 14 patients). No re-perforations or extrusions of the prostheses were observed.
Gesehen am 05.05.2023